A systematic review on career interventions for high school students - Wang, Danqi; Li, Yanling; Wang, Gang (Frontiers in Psychology, 2024)
This study presents a systematic literature review of career interventions for high school students, exploring the theoretical framework, intervention modality, evaluation and outcomes of the intervention. Five keywords, three databases and five inclusion criteria were defined. Of the 419 documents collected, 25 remained for meta-synthesis.The results showed that (1) the theoretical framework mainly consisted of career construct theory, social cognitive career theory, and cognitive information processing theory. ( 2) The intervention modality was mainly group counselling (8 sessions, 45 min). (3) The evaluation system mainly consisted of a pre-and post-test for the experimental and control group, and (4) The intervention outcomes were mainly focused on the positive development of career adaptability and career decision-making. The discussion offers recommendations for future research and practice in high school career interventions. (1) Social cognitive career theory should be given attention. (2) A three-tiered high school career development guidance model of career curriculum, career group counselling and individual counselling could be developed. (3) Career interventions should be shifted to mixed quantitative and qualitative studies, tracer studies, and special groups. (4) Outcome expectations should be given equal attention.